Media Pengenalan Budaya Besemah Berbasis Augmented Reality Menggunakan Metode MDLC - Lendy Rahmadi; Heriansyah Heriansyah; Hairil Akbar (Jurnal Publikasi Ilmu Komputer dan Multimedia, 2025)
This research aims to design and develop an Augmented Reality (AR)-based application as a medium for introducing and learning Besemah culture, particularly for the community of Pagar Alam City. Besemah culture, rich in history and traditions, is increasingly forgotten due to globalization and the lack of attractive media. The proposed application presents interactive information about traditional houses, traditional clothing, musical instruments, and local traditions. The development process follows the Multimedia Development Life Cycle (MDLC) method, consisting of six stages: concept, design, material collection, assembly, testing, and distribution. The results show that the application can display 3D cultural objects and provide cultural information interactively, making it easier for users to learn about Besemah culture. Black-box testing indicates that all application functions run as expected, while beta testing with community participants shows positive responses to usability and content quality. This research is expected to contribute to the preservation of local culture and serve as an innovative educational medium for the younger generation.